Dari Hutan Purba Menjadi Perkebunan - Itawan, Devi - (Jurnal Sejarah, 2020)
This article aims to explore the use of photographs to reconstruct the colonial capitalist modes of production of the past effected on the landscape. The penetration of capitalism signified by the expansion of the plantation has brought about the major transformation on the East Coast Sumatra's landscape that can be traced with photographs. Basically, the visualization and publication of the production process by the plantation's company and its association were aimed to shape the image of the plantation as a prosperity bearer in the colony of East Coast of Sumatra. Nevertheless, the photos revealed the dark sides of the exploitation of natural resources on a massive scale. The plantation photographs showed deforestation, land-use changes, and plantation expansion that became a tangible footprint of the colonial exploitation in the East Coast of Sumatra.